TIPICO IX: report of the 9th interactive infectious disease workshop on infectious diseases and vaccines. Issue 10 (3rd October 2019) - Martinón-Torres, Federico; Bosch, Xavier; Rappuoli, Rino; Ladhani, Shamez; Redondo, Esther; Vesikari, Timo; García-Sastre, Adolfo; Rivero-Calle, Irene; Gómez-Rial, José; Salas, Antonio; Martín, Carlos; Finn, Adam; et al.
ABSTRACT: The Ninth Interactive Infectious Disease workshop TIPICO was held on November 22–23, 2018, in Santiago de Compostela, Spain. This 2-day academic experience addressed current and topical issues in the field of infectious diseases and vaccination. Summary findings of the meeting include: cervical cancer elimination will be possible in the future, thanks to the implementation of global vaccination action plans in combination with appropriate screening interventions. The introduction of appropriate immunization programs is key to maintain the success of current effective vaccines such as those against meningococcal disease or rotavirus infection. Additionally, reduced dose schedules might improve the efficiency of some vaccines (i.e., PCV13). New vaccines to improve current preventive alternatives are under development (e.g., against tuberculosis or influenza virus), while others to protect against infectious diseases with no current available vaccines (e.g., enterovirus, parechovirus and flaviviruses) need to be developed. Vaccinomics will be fundamental in this process, while infectomics will allow the application of precision medicine. Further research is also required to understand the impact of heterologous vaccine effects. Finally, vaccination requires education at all levels (individuals, community, healthcare professionals) to ensure its success by helping to overcome major barriers such as vaccine hesitancy and false contraindications.